PEREMPUAN PENYAPU JALAN DI KOTA PASIR PENGARAIAN KECAMATAN RAMBAH KABUPATEN ROKAN HULU - Mareza "; Hesti Asriwandari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research was carried out in the City of Pasir Pengaraian,Rambah Sub District,Rokan Hulu Regency.The purpose of this study was to find out the profile of street sweeper women and the reasons for working as a sreetsweeper. The focus of this research is to analyze the factors that encourage women street sweepers to work in City of Pasir Pengaraian. The theory used in this study uses 1 theories, namely Role Theory. The data collection techniques of this study  were interviews,questionnaires and documentation.The sample  used in this study amounted to 52 respondents, all of which were street sweepers, the method used in this study was quantitative descriptive. The results of this study indicate that 1). That women sreet sweepers in Pasir Pengaraian City almost spent their time outside 2).The reason women sreet sweepers work is because of the demands of life that cause economic pressure,besides that work also becomes a place to overcome boredom for research subjects. In this study the income of a female street sweeper was Rp.1,475,000, where their income is allocated to cover the costs of their children’s school besides working as a street sweeper,they can fulfill the needs of family members and themselves Keywords: Sreet Sweeper,Duel Role,Woman